2017
DOI: 10.18632/oncotarget.22748
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel genes in aging osteoblasts using next-generation sequencing and bioinformatics

Abstract: During the aging process, impaired osteoblastic function is one key factor of imbalanced bone formation and age-related bone loss. The aim of this study is to explore the differentially expressed genes in normal and aged osteoblasts and to identify genes potentially involved in age-related alteration in bone physiology. Based on next generation sequencing and bioinformatics analysis, 12 differentially expressed microRNAs and 22 differentially expressed genes were identified. Up-regulation of miR-204-5p was val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Recent studies discovered that the TF SREBP2 can promote osteoclast differentiation by affecting the expression of RANKL ( Inoue and Imai, 2014 ). Through bioinformatics analysis, miR-204-5p was found as a key regulator to alter bone health condition in the elderly, while KLF7 was identified as a target gene of miR-204-5p ( Chen et al, 2017 ). Similarly, by utilizing bioinformatics approaches and ChIP assay, this study found that TF KLF7 could bind HO-1 and their expression was negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies discovered that the TF SREBP2 can promote osteoclast differentiation by affecting the expression of RANKL ( Inoue and Imai, 2014 ). Through bioinformatics analysis, miR-204-5p was found as a key regulator to alter bone health condition in the elderly, while KLF7 was identified as a target gene of miR-204-5p ( Chen et al, 2017 ). Similarly, by utilizing bioinformatics approaches and ChIP assay, this study found that TF KLF7 could bind HO-1 and their expression was negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study manifested that the overexpression of KLF7 in bone marrow stromal stem cells can promote the regeneration of sciatic nerve ( Li et al, 2019 ). Recently, a bioinformatics study suggested that KLF7 can affect patient’s BMD, which makes it a key target of osteoporosis ( Chen et al, 2017 ). Due to the limitations of bioinformatic studies, the biological role of KLF7 in osteoporosis has not been fully elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Mitchell et al suggested that three candidate variants in ADRB2, TLR4 and CFH are associated with heterotopic ossification (48). SEMA3A was reported to play a role in neurogenic heterotopic ossification (49). However, ACVR1 and GNAS were not found in a mesenteric heterotopic ossification patient, although they were reported to have a potential connection to heterotopic ossification (50-52).…”
Section: Discussionmentioning
confidence: 99%
“…However, this ability declines with advancing age, which is now known as stem cell exhaustion, identified as one of the key hallmarks of aging [4,17]. Whilst the different stem cells and immune cells all coexist within the BM niche, how their functions are altered with advancing age have been investigated separately [19]. This section summarises the changes associated with aging amongst the various cell types and the BM in general.…”
Section: Aging In the Bone Marrowmentioning
confidence: 99%
“…However, a technique that can provide us with a large amount of data at the genetic level for the identification of new pathways would be ideal for evaluating age-related changes in the BM. Next-generation sequencing (NGS) provides us with exactly that, making it among the most desirable techniques for studying changes with advancing age [18,19].…”
Section: Introductionmentioning
confidence: 99%